Online Self-Regulated Learning Assisted by Virtual Labs to Train STEM Student's Critical Thinking Skills - Ernita, Nevi; Bahtiar, Bahtiar; Zulkarnaen, Zulkarnaen; Mustofa, Hisbulloh Als; Faresta, Rangga Alif (International Journal of Essential Competencies in Education, 2024)
This study investigated the effectiveness of integrating online self-regulated learning with virtual labs in enhancing critical thinking skills among STEM students. The research adopted a controlled experimental design involving two groups—experimental and control—over a two-month period, employing a mix of interactive virtual labs and structured online self-regulated learning strategies for the former, while maintaining traditional educational methods for the latter. Results indicated significant improvements in the experimental group's critical thinking capabilities across multiple indicators such as interpretation, analysis, evaluation, inference, explanation, and self-regulation, compared to modest improvements in the control group. The experimental group benefited from a dynamic and interactive learning environment that allowed for hands-on experiments and simulations, fostering a deeper understanding and engagement with scientific concepts. This environment, enhanced by the strategic application of self-regulated learning techniques, facilitated a more effective development of critical thinking skills than traditional methods. The study highlighted the potential of virtual labs combined with self-regulated learning to significantly enhance educational outcomes in STEM education, suggesting that such integrative approaches could better prepare students for the complexities of the modern scientific landscape. Additionally, the study underscored the need for future research to explore these strategies across a more diverse and broader educational context to confirm these findings and further refine the educational interventions employed.